Security Examination Procedures in the New Normal Period and Performance of Aviation Security Officers at Morowali Airport, Central Sulawesi Province - Moh Ikhlasul Amal; Ristiani Ristiani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Aviation Security officers play an important role in carrying out inspections to maintain the security and safety of prospective passengers. In the initial interview with AVSEC officers at Morowali Airport, Central Sulawesi Province, changes in policy, especially in the New Normal Era, can affect the performance of AVSEC officers, apart from conducting security checks on passengers, AVSEC officers also direct passengers who have or are identified with symptoms of COVID-19 to checked separately and also carry out separate checks on passengers who carry sharp weapons or firearms that can threaten and endanger flight security and safety. With this additional performance, it can affect the performance of AVSEC officers, apart from conducting security checks, officers also conduct briefings for passengers. This study aims to find out the security inspection procedures during the new normal period at Morowali Airport, Central Sulawesi Province. And analyze the performance of Aviation Security (AVSEC) officers at Morowali Airport, Central Sulawesi Province. This study uses a qualitative approach with data collection techniques using observation methods, structured interviews, and documentation collected from relevant informants when the writer is in the field. The results of this study indicate that the inspection procedure in the era of adaptation to new habits is the same as the previous examination but there are additional checks or rules such as passengers must wear masks, maintain a minimum distance of 1 meter and examine health documents for passengers who will travel with the help of supporting equipment such as Walk Through Metal Detector, Hand Held Metal Detector, X-Ray Machine. And the performance of Aviation Security personnel at Morowali Airport is in accordance with the SOP set at Morowali Airport, Central Sulawesi.